2016
DOI: 10.28945/3411
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Primary Learning Style for Children with Secondary Behavioral Patterns

Abstract: Personalization is one of the most expected features in the current educational systems. User modeling is supposed to be the first stage of this process, which may incorporate learning style as an important part of the model. Learning style, which is a non-stable characteristic in the case of children, differentiates students in learning preferences. This paper identifies a new hybrid method to initiate and update the information of children's learning style in an educational system. At the start-up phase, chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Study [ 47 ] cluster/detect learner model in order to assess the preferable adaptation strategies without implementing any adaptation. Studies [ 39 , 56 ] showed the importance of learning style correction through a dynamic learner model; however, the corresponding adaptation strategies were not investigated. Studies [ 11 , 18 ] focus on the content adaptation based on static learner model for cognitive level detection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study [ 47 ] cluster/detect learner model in order to assess the preferable adaptation strategies without implementing any adaptation. Studies [ 39 , 56 ] showed the importance of learning style correction through a dynamic learner model; however, the corresponding adaptation strategies were not investigated. Studies [ 11 , 18 ] focus on the content adaptation based on static learner model for cognitive level detection.…”
Section: Literature Reviewmentioning
confidence: 99%